Intermediate mass black hole formation in compact young massive star clusters - Rizzuto, Francesco Paolo; Naab, Thorsten; Spurzem, Rainer; Giersz, Mirek; Ostriker, J. P.; Stone, N. C.; Wang, Long; Berczik, Peter; Rampp, M. (Monthly notices of the Royal Astronomical Society, 2021)
Young dense massive star clusters are promising environments for the formation of intermediate mass black holes (IMBHs) through collisions. We present a set of 80 simulations carried out with nbody6gpu of 10 models of compact $\sim 7 × 10^4 \, M_{\odot }$ star clusters with half-mass radii Rh ≲ 1 pc, central densities $ρ _core \gtrsim 10^5 \, M_\odot \, pc^{-3}$, and resolved stellar populations with 10 per cent primordial binaries. Very massive stars (VMSs) up to $\sim 400 \, M_\odot$ grow rapidly by binary exchange and three-body scattering with stars in hard binaries. Assuming that in VMS-stellar black hole (BH) collisions all stellar material is accreted on to the BH, IMBHs with masses up to $M_BH \sim 350 \, M_\odot$ can form on time-scales of ≲15 Myr, as qualitatively predicted from Monte Carlo mocca simulations. One model forms an IMBH of 140 $\mathrm{M_{\odot }}$ by three BH mergers with masses of 17:28, 25:45, and 68:70 $\mathrm{M_{\odot }}$ within ∼90 Myr. Despite the stochastic nature of the process, formation efficiencies are higher in more compact clusters. Lower accretion fractions of 0.5 also result in IMBH formation. The process might fail for values as low as 0.1. The IMBHs can merge with stellar mass BHs in intermediate mass ratio inspiral events on a 100 Myr time-scale. With 105 stars, 10 per cent binaries, stellar evolution, all relevant dynamical processes, and 300 Myr simulation time, our large suite of 80 simulations indicate another rapid IMBH formation channel in young and compact massive star clusters.
Gesehen am 16.06.2021
First published: 21 November 2020